Peran Kecerdasan Emosional dalam Kepemimpinan Pendidikan: Analisis Bibliografi 2000-2025 - Ulya, Zihniatul; Munir Abidin (Program Studi Pendidikan Luar Sekolah, 2025)
Abstract: This study analyzes the role of emotional intelligence in educational leadership through a systematic bibliographic analysis of the literature published between 2000 and 2025. Successful leadership depends not only on cognitive intelligence, but also on the ability to manage emotions, self-restraint, be highly motivated, understand the emotions of others, empathy, creativity, and tolerance. In the context of education, leaders must be able to inspire and motivate staff and learners, where intellectual capacity and managerial skills alone are not enough without emotional intelligence. Emotional intelligence, according to Goleman, includes the ability to recognize and manage one's own emotions and others, motivate, and build positive social relationships. Although many studies have addressed aspects of emotional intelligence in educational leadership, there is still no comprehensive bibliographic analysis integrating these findings. This research aims to fill this gap by using quantitative methods and bibliometric analysis on data taken from Scopus from 2000 to 2025. The keywords used were